Etiologic factors associated with Achilles tendinitis in runners - McCrory, J. L.; Martin, D. F.; Lowery, R. B.; Cannon, D. W.; Curl, W.; Read, H. M.; Hunter, D. M.; Craven, T.; Messier, S. P. (Medicine & Science in Sports & Exercise, 1999)
PURPOSE: The purpose of this study was to determine whether relationships exist between selected training, anthropometric, isokinetic muscular strength, and endurance, ground reaction force, and rearfoot movement variables in runners afflicted with Achilles tendinitis. METHODS: Specifically, we examined differences in selected measures between a noninjured cohort of runners (N = 58) and a cohort of injured runners with Achilles tendinitis (N = 31). Isokinetic, kinetic, and kinematic measures were collected using a Cybex II+ isokinetic dynamometer (Medway, MA), AMTI force plate (500 Hz), and Motion Analysis high-speed videography (200 Hz), respectively. Separate discriminant function analyses were performed on each of the five sets of variables to identify the factors that best discriminate between the injured and control groups. RESULTS: Years running, training pace, stretching habits (injured runners were less likely to incorporate stretching into their training routine), touchdown angle, plantar flexion peak torque at 180 degrees x s(-1) and arch index were found to be significant discriminators. CONCLUSION: A combined discriminant analysis using the above mentioned significant variables revealed that plantar flexion peak torque, touchdown angle, and years running were the strongest discriminators between runners afflicted with Achilles tendinitis and runners who had no history of overuse injury.